Multicenter Evaluation of a Novel Automated Rapid Detection System of BRAF Status in Formalin-Fixed, Paraffin-Embedded Tissues - Schiefer, Ana-Iris; Parlow, Laura; Gabler, Lisa; Mesteri, Ildiko; Koperek, Oskar; Deimling, Andreas von; Streubel, Berthold; Preusser, Matthias; Lehmann, Annika; Kellner, Udo; Pauwels, Patrick; Lambin, Suzan; et al. (The journal of molecular diagnostics, 2016)
The mutated BRAF oncogene represents a therapeutic target in malignant melanoma. Because BRAF mutations are also involved in the pathogenesis of other human malignancies, the use of specific BRAF inhibitors might also be extended to other diseases in the future. A prerequisite for the clinical application of BRAF inhibitors is the reliable detection of activating BRAF mutations in routine histopathological samples. In a multicenter approach, we evaluated a novel and fully automated PCR-based system (Idylla) capable of detecting BRAF V600 mutations in formalin-fixed, paraffin-embedded tissue within 90 minutes with high sensitivity.